Interpretative challenges in face analysis - Sandi Michele de Oliveira; Nieves Hernández-Flores (Textos en Proceso, 2015)
In current research on face analysis questions of who and what should be interpreted, as well as how, are of central interest. In English language research, this question has led to a debate on the concepts of P1 (laypersons, representing the “emic” perspective) and P2 (researchers, representing the “etic”). In our view, two points seem critical: a) are P1 and P2 sufficiently well described to be of use in the broader analytical context that is face analysis today? And b) what contribution does this distinction make towards a greater understanding of the data?  From our research on facework in Spanish and address forms in European Portuguese, we view P1 and P2 as being far more complex than the literature suggests, with subgroups (different types of laypersons and researchers, respectively). At the micro-level we will describe the roles each subgroup plays in the interpretative process; at the macro-level we discuss how P1 and P2 are integrated into the global interpretation of face. While researchers of face analysis work typically consider P1 and P2 as independent categories, we believe the contributions of P1 and P2 cannot be disassociated. Both must be taken into account in the global analysis and final interpretative framework.